The East Timorese Global Solidarity Movement, State Denial, and the Human Rights Strategy: Discourse, State Power, and Political Mobilization - Torelli, Julian (My University, 2023)
A small island nation near Australia was invaded and occupied by the Indonesian military regime in 1975, which lasted until 1999. This dissertation examines the global solidarity movement, whose success was due to the skill of its leaders, the collective agency transnational mobilization, effective social movement framing, which helped to create, act upon, and transform important critical junctures throughout the conflict. The East Timorese resistance movement against the Indonesian occupation took an ethnically and politically fragmented society and transformed it into a powerful transnational resistance movement that brough together military, clandestine, diplomatic, and global civil society actors together in supporting East Timor’s right to self-determination. Social movement frames punctuate the severity, immorality, and injustice of conditions. However, existing accounts on claims-making, framing trajectories, and outcomes tend to downplay the influence of contingency and indeterminacy in social movements. Indeed, as social constructionists contend, collective constructions are historically produced and culturally contingent. As claims-makers advance public claims developed within institutional realities, this underscores the range of contingencies and uncertainties actors manage in mobilizing their agendas. With East Timor's case, this sandwich thesis contends that understanding social movement framing and trajectories requires keeping institutional, discursive, and geopolitical contexts intact. Movements are embedded in histories, institutions, or fields that shape the outcome of framing trajectories and the outcome of social movement claims-making. However, social constructionists help us understand that resources, frames, and opportunities are perceived and constructed by actors. Therefore, the theoretical perspective provides substantial credence to the roles of contingency and human agency in social movement mobilization. Ultimately, objective structures, such as political/discursive opportunities or legal texts, are not enabling but generate social movement action insofar as moral agents perceive them. Often, this work is discursively constructed. This reality underscores the dimension of contingency in social action and social movement framing and mobilization because objective structures do not automatically determine what actors will select as a specific course of collective action or framing strategies. Frame and framing trajectories are particular to, and instantiated in, the contexts and develop over time as moral agents mobilize meaning by interacting with targets, sensitive to local conditions, emergent contingencies, and competing interests. By focusing on the social framing process, I show how framing or collective action frames emerge and are diffused in different ways across national contexts. The emphasis is not to address the broader institutionalized logics, such as political/discursive opportunities and geopolitics, but to understand how these aspects are incorporated in the framing practices of moral agents as strategic action as “endogenous to a field of actors” (Lounsbury et al., 2003:72), whose interests and national, not only transnational, but embeddedness also influence the interactional dynamics of their framing actions and trajectories. In this way, framing practices can be understood as struggles over audiences' minds and hearts, where actors compete in moral politics to secure symbolic power and political legitimacy. The macro-level logic indeed impacts the structure of frames. The diffusion and acceleration of claims within historically contingent events depend simultaneously on pre-existing, strong cultural framing and an influential social movement culture rooted in the abstract ideals of human rights that are transnationally dispersed but integrated. Strategic framing choices depend on various logic. Firstly, expanding political and discursive opportunities is crucial in accelerating mobilization. Moreover, the diffusion of frames and public claims can further propel mobilization and help to build convergences across sociopolitical allies. Agency and structure are often interpenetrating. Namely, depending on the choices made by actors at specific ‘critical junctures,’ they can either propel the social force of mobilization or hamper it, depending on perceived choices (agency). Social movements, especially transnational advocacy networks, prove more effective in frame diffusion when they build solidarities around shared meaning and international norms (human rights) that allow them to converge effectively around shared purposes and sustain collective mobilization across extended periods. Transnational networks of solidarity (the global solidarity movement) harnessed collective mobilization at the global level by converging the diffusion of their frames and claims around human rights talk. The thesis also considers various logics such as path dependency, contingency, historical events, and geopolitics in shaping the national and global movement mobilization and claims-making field.
Keywords: East Timor, Global Solidarity, Framing, Human Rights